2013
DOI: 10.1002/ddr.21078
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Structure/Pharmacophore‐Based Virtual Screening Approach to Design Potential Leads: A Computer‐Aided Design of South African HIV‐1 Subtype C Protease Inhibitors

Abstract: Preclinical Research Virtual screening is the computational mirror image of high‐throughput screening and refers to the in silico evaluation of the biological activity of different molecular entities. Various virtual screening strategies and workflows have been adopted to enhance the process of identification of potential hits. Structure‐based scoring relies solely on the interactions between the ligand and the target protein. Conversely, pharmacophore‐based scoring relies on the shape complementation of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Coumarinyl pyrazolinyl thioamides 5a – 5q depict good intestinal solubility results compared to standard value (> 30% abs). Literature study showed that a compound with less than 30% absorbance value is considered as poorly absorbed compound . The skin permeability values of all compounds were also greater than standard value (−2.5 log K p ) which showed their significance as a good lead structures and justified their drug likeness behavior.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Coumarinyl pyrazolinyl thioamides 5a – 5q depict good intestinal solubility results compared to standard value (> 30% abs). Literature study showed that a compound with less than 30% absorbance value is considered as poorly absorbed compound . The skin permeability values of all compounds were also greater than standard value (−2.5 log K p ) which showed their significance as a good lead structures and justified their drug likeness behavior.…”
Section: Resultsmentioning
confidence: 88%
“…Literature study showed that a compound with less than 30% absorbance value is considered as poorly absorbed compound. [23] The skin permeability values of all compounds were also greater than standard value (À2.5 logK p ) which showed their significance as a good lead structures and justified their drug likeness behavior. Moreover, Blood Brain Barrier (BBB) and Central Nervous System (CNS) permeability values of all screened compounds were also comparable with the standard values (> 0.3 to <À1 log BB and >À2 to <À3 logPS), respectively.…”
Section: Bio-chemical Properties and Ro5 Validation Of Synthesized Comentioning
confidence: 80%
See 1 more Smart Citation
“…The program generates initial 3D structures from a library of fragments, then it exhaustively enumerates all rotatable torsions using pre-defined libraries, and finally it samples this large conformational space using geometric and energy criteria. As an example, potential inhibitors of HIV-1 protease have been designed by the combination of conformational search with Omega and docking with Autodock [62].…”
Section: Monte Carlo (Mc) Search Methodsmentioning
confidence: 99%
“…The pharmacoinformatics approaches including structure activity relationship (SAR), pharmacophore, virtual screening and molecular docking have become pivotal techniques in the pharmaceutical industry for lead discovery. Many groups have applied the pharmacoinformatics approaches to identify inhibitors [23][24][25][26][27][28][29] against HIV protease. Hence the current study explores the binding preferences of the inhibitory molecules of HIV protease in terms of space modelling study and virtual screening along with molecular docking.…”
Section: Introductionmentioning
confidence: 99%